2022
DOI: 10.3390/e24081114
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Teleportation and Dense Coding in Multiple Bosonic Reservoirs

Abstract: The effect of a reservoir on quantum communication depends on its spectral density. The efficiency of quantum teleportation and dense coding is explored when each one of the channel qubits is coupled simultaneously to multiple bosonic reservoirs. It is shown that the non-Markovianity triggered by increasing the reservoir number can induce revivals of quantum advantages of the two protocols after their disappearance. However, the backflow of information to the system that signifies non-Markovianity does not alw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Many algorithms such as Deutsch-Jozsa, Bernstein-Vazirani, Simon, quantum Fourier transform, quantum phase estimation, quantum counting, quantum walk search, and dense coding are being investigated. [86][87][88][89][90][91]…”
Section: Quantum Algorithmsmentioning
confidence: 99%
“…Many algorithms such as Deutsch-Jozsa, Bernstein-Vazirani, Simon, quantum Fourier transform, quantum phase estimation, quantum counting, quantum walk search, and dense coding are being investigated. [86][87][88][89][90][91]…”
Section: Quantum Algorithmsmentioning
confidence: 99%
“…In the literature, several studies have both theoretically proposed and experimentally demonstrated the concept of dense coding (see, e.g., [9][10][11][12][13][14][15][16][17] and references quoted therein). Interestingly, different methods have been presented to protect the quantum advantages of dense coding under decoherence for a relatively long time [18][19][20][21][22][23], such as choosing the proper initial channel state [24,25], employing different configurations for the external noise [26,27], and applying the quantum weak measurement (QWM) operation [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…To be teleported, quantum states must be exposed to an external environment [29][30][31]. Several classical and quantumtype channels have recently been used to assess teleportation, quantum correlation dynamics, and preservation success [32][33][34][35][36][37][38][39][40][41][42][43][44]. The phonon baths, in combination with a nonmechanical resonator, are one of the best-performing cavities which have been found [45][46][47].…”
Section: Introductionmentioning
confidence: 99%